Absorbable scaphoid screw development: a comparative study on biomechanics - Wang Y; Song MG; Xu YQ; He XQ; Zhu YL (Dove Medical Press, 2016)
Yi Wang, Muguo Song, Yongqing Xu, Xiaoqing He, YueLiang Zhu Department of Orthopedic Surgery, Kunming General Hospital, Chengdu Military Command, People’s Liberation Army, Kunming, Yunnan, People’s Republic of China Background: The scaphoid is critical for maintaining the stability and movement of the wrist joints. This study aimed to develop a new internal fixator absorbable scaphoid screw (ASS) for fixation of the scaphoid waist after fracture and to test the biomechanical characteristics of ASS.Materials and methods: An ASS was prepared using polylactic acids and designed based on scaphoid measurements and anatomic features. Twenty fractured scaphoid waist specimens were randomly divided into experimental and control groups (n=10/group). Reduction and internal fixation of the scaphoid were achieved with either Kirschner wires (K-wires) or ASS. A moving target simulator was used to test palmar flexion and dorsal extension, with the range of testing (waist movement) set from 5° of palmar flexion to 25° of dorsal extension. Flexion and extension were repeated 2,000 times for each specimen. Fracture gap displacements were measured with a computerized tomography scanning. Scaphoid tensile and bending strengths were measured by using a hydraulic pressure biomechanical system.Results: Prior to biomechanical fatigue testing, fracture gap displacements were 0.16±0.02 mm and 0.22±0.02 mm in the ASS and K-wire groups, respectively. After fatigue testing, fracture gap displacements in the ASS and the K-wire groups were 0.21±0.03 mm and 1.52±0.07 mm, respectively. The tensile strengths for the ASS and K-wire groups were 0.95±0.02 MPa and 0.63±0.02 MPa, respectively.Conclusion: Fixation using an ASS provided sufficient mechanical support for the scaphoid after fracture. Keywords: absorbable scaphoid screw, biomechanics, internal fixator, Kirschner wires